USM 2ND AMBASSADORS SUMMIT 2015 TO ENHANCE INTERNATIONAL STRATEGIC RELATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 11 September 2015 – The organisation of an intellectual discourse with the participation of foreign ambasssadors in the country in the Universiti Sains Malaysia (USM) 2nd Ambassadors Summit 2015 can be seen as an initiative in enhancing strategic relations between the respective countries, more specifically in areas of higher education.